Immunogenicity associated with metreleptin treatment in patients with obesity or lipodystrophy - Chan, Jean L. (Clin Endocrinol (Oxf), 2016)
OBJECTIVE: Recombinant human leptin (metreleptin) improves glycemia and hypertriglyceridemia in patients with generalized lipodystrophy; antibody development with in vitro neutralizing activity has been reported. We aimed to characterize anti-metreleptin antibody development, including in vitro neutralizing activity. DESIGN: Two randomized controlled studies in patients with obesity (twice-daily metreleptin ± pramlintide for 20–52 weeks; 2006–2009); two long-term, open-label studies in patients with lipodystrophy (once-daily or twice-daily metreleptin for 2 months to 12.3 years; 2000–2014). PATIENTS: 579 metreleptin-treated patients with obesity, 134 metreleptin-treated patients with lipodystrophy (antibody/neutralizing activity data: n=105). MEASUREMENTS: Anti-metreleptin antibodies, in vitro neutralizing activity. RESULTS: Anti-metreleptin antibodies developed in most patients (obese: 96–100%; lipodystrophy: 86–92%). Peak antibody titers (~1:125 to 1:3125) generally occurred within 4–6 months and decreased with continued therapy (lipodystrophy). Antibody development did not adversely impact efficacy or safety (patients with obesity), except for inflammatory injection site reactions, but was associated with elevated leptin concentrations. Three patients with obesity developed in vitro neutralizing activity coincident with weight gain. Weight later returned to baseline in one patient despite persistent neutralizing activity. Four patients with generalized lipodystrophy developed in vitro neutralizing activity concurrent with worsened metabolic control; two with confounding comorbidities had sepsis. One patient with lipodystrophy had resolution of neutralizing activity on metreleptin. CONCLUSIONS: Development of in vitro neutralizing activity could be associated with loss of efficacy but has not been consistently associated with adverse clinical consequences. Whether neutralization of endogenous leptin with clinical consequences occurs remains unclear.